Nginig ([Quezon City] ABS-CBN, 2004)
Pagbabalik sa guho : a storm revanges the residents of San Francisco Leyte. But even beyond death, three souls prove that promises are mean to be kept. A bride comes back from the dead to ease her beloved's pain... A woman's ghost 'Wathces over' her friends sari-sari store, keeping strangers out.
Chop-chop lady : Passion and jealousy drive a man to kill his best friend, kidnap his bride on her wedding day and chop her to pieces. Now the brides grieving soul haunts an apartment building in Caloocan, seeking bloody justice for her painful death.
Pagbabalik sa guho ; Chop-chop Lady
VCD
Keywords: Horror Films; documentary--Films.; Drama; Feature films